The Service Quality Of Cahaya Terang Laundry Business At 53 Cempaka Street, Kebun Beler, Bengkulu City - Nirmalawati, Nirmalawati; Susena , Karona Cahya; Abi , Yudi Irawan (Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Service quality is paramount in the service industry providing the best service quality is a profitable strategy for attracting more new customers, retaining existing ones, avoiding customer churn, and creating unique advantages beyond competing solely on price. When the service received or perceived aligns with customer expectations, it leads to favorable perceptions of service quality and satisfaction. The success of a company is heavily influenced by how it satisfies and delights its customers. As an entity within a system, a company focuses its activities on customers as service consumers to operate more effectively and efficiently in delivering or providing high-quality services or products as per customer expectations. On the other hand, a company as a system also needs to ensure the happiness of its internal customers, in this case, the employees (service producers). This is aimed at producing services that meet the expectations of external customers. From the five dimensions of service quality used to assess service quality at "Cahaya Terang" laundry, namely Tangibles, Reliability, Responsiveness, Assurance, and Empathy, it can be concluded that the service quality at "Cahaya Terang" laundry is excellent. This can be seen from the results of interviews conducted by researchers with the informants. "Cahaya Terang" laundry continually improves its quality to create mutually beneficial relationships for both customers and service providers continuously.